Prescription pattern of antibiotic usage for urinary tract infection treated in a rural tertiary care hospital. - KV, Ramanath; SB, Shafiya (Indian Journal of Pharmacy Practice)
Urinary tract infections are the second most common infectious disease in the community medical practice. The objective was to study the prescription pattern of antibiotics used in the treatment of UTI. A prospective cross sectional study was conducted on patients diagnosed with UTI. The study was carriedout in the General medicine, OBG, Surgery and Urology departments of both in-patients and out-patients, for a period of 9 months (June 2010 to Feb 2011). Urinary Tract Infection patients who were in the age group of 18-80 years were included after obtaining their informed consent. A suitable data collection form was prepared and used to collect the required data. Among 136 patents, 41 were inpatients and 95 were out-patients. Most of the in-patients were prescribed with Ceftriaxone 28(68.3%), Cefotaxim 5(12.2%), and Ciprofloxacin 3 (7.3%) respectively. In out-patients, Ciprofloxacin 27(28.4%), Norfloxacin 21(22.1%) and Nitrofurantoin 18(18.9%) were prescribed respectively. The study found that gram negative organisms like E. coli was the most predominant organism. It was also found that Cephalosporin's were most commonly used and Quinolones were the second most commonly used drugs for the treatment of UTI. The third category drug used in UTI female patients was nitrofurantoin which is relatively inexpensive and safe for both pregnant and non- pregnant women.
Keywords: Urinary tract infection; Antibiotics; Prescription